Correction to: The development and validation of a “5A” severity scale for predicting in-hospital mortality after accidental hypothermia from J-point registry data - Yohei Okada; Tasuku Matsuyama; Sachiko Morita; Naoki Ehara; Nobuhiro Miyamae; Takaaki Jo; Yasuyuki Sumida; Nobunaga Okada; Makoto Watanabe; Masahiro Nozawa; Ayumu Tsuruoka; Yoshihiro Fujimoto; et al. (Journal of Intensive Care, 2019)
In the original publication of this article [1], the figure legends of Fig. 2 and Fig. 3 are wrong and should be changed as below: